IMPLEMENTATION OF HEALTH SERVICES FOR PRISONERS WITH HUMAN IMMUNODEFICIENCY VIRUS (HIV) IN CLASS IIA PURWOKERTO CORRECTIONAL INSTITUTION - Saputra, Mico Jeje; Biafri, Vivi Sylviani (Universitas Nusa Cendana, 2025)
This study aims to determine the implementation of health services for the fulfillment of human immunodeficiency virus (HIV) sufferers in Class IIA Purwokerto Correctional Institution. This study focuses on the provision of health services, including medical care, counseling, and support, to ensure the well-being of people with HIV. The research methodology uses a qualitative approach to explore the health services currently available, identify challenges faced, and recommend improvements needed to improve the quality of life of compensation for people with HIV. Data analysis conducted involved in-depth interviews with health assistants and prison administrators to understand their perspectives on the implementation of health services. The findings of this study are important in informing policies and practices that promote human rights and assisting people with HIV in Indonesian correctional institutions. Keywords: Health Services; Implementation; Human Immunodeficiency Virus (HIV)